Welfare and Poverty Impacts of India's National Rural Employment Guarantee Scheme : Evidence from Andhra Pradesh - Deininger, Klaus; Liu, Yanyan (World Bank, Washington, DC, 2013)
This paper uses a three-round 4,000-household panel from Andhra Pradesh together with administrative data to explore short and medium-term poverty and welfare effects of the National Rural Employment Guarantee Scheme. Triple difference estimates suggest that participants significantly increase consumption (protein and energy intake) in the short run and accumulate more nonfinancial assets in the medium term. Direct benefits exceed program-related transfers and are most pronounced for scheduled castes and tribes and households supplying casual labor. Asset creation via program-induced land improvements is consistent with a medium-term increase in assets by nonparticipants and increases in wage income in excess of program cost.